Eros as Educator in the Era of Advanced Monetary Economy: Simmel’s Social Metaphysics of the Erotic Being - Christias, Panagiotis (Simmel Studies, 2019)
In the era of advanced monetary economy, the nexus of love, money, and good education is at the origin of the “good society”. If marriage was invented for reasons of administration of goods and money, then the fact that individual love came upon marriage in the specific historical and geographical context of the Western European metropolitan life cannot be a coincidence. The platonic ladder of love, that leads to eternity through the erotic elevation of the soul to the sight of the Ideas, is transformed in Modern era through the new perception of Money as a “secular god”. For Plato, the goal of the lover is actually “education” (paideia) as he is supposed to give to the soul of the beloved wings in order to elevate itself to the contemplation of the Ideas. Plato’s heritance regarding love, says Simmel, is the belief that beyond the affect something of a bigger order is hiding in the phenomenon of love. As long as serial monogamy is the dominant model of erotic relations in our days, it is clear that its spiritual background is linked to Platonic Eros, not as an initiation to the science of the general, but, bended by the modern understanding of the individual, as an art of the individual. What is explored in this article is the educational role of Eros and its cultural potential. Eros can actually be considered as educator, as the initiator of the individual to a higher collective and spiritual order.